2022
DOI: 10.1007/s11060-022-04042-3
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic imaging of D-2-hydroxyglutarate and other metabolites in pre-surgical patients with IDH-mutant lower-grade gliomas

Abstract: Purpose Prognostically favorable IDH-mutant gliomas are known to produce oncometabolite D-2-hydroxyglutarate (2HG). In this study, we investigated metabolite-based features of patients with grade 2 and 3 glioma using 2HG-specific in vivo MR spectroscopy, to determine their relationship with image-guided tissue pathology and predictive role in progression-free survival (PFS). Methods Forty-five patients received pre-operative MRIs that included 3-D spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
4
1
1
Order By: Relevance
“…Consistent with clinical experience, Tiwari et al [3] found that lower survival risk was associated with higher levels of 2-HG and the presence of IDH mutations. Interestingly, Autry et al [18] revealed that higher levels of 2-HG/Cr indicated a significant reduction in PFS, which contradicts our clinical impression. However, this study enrolled patients with IDH mutations, suggesting that in patients with IDH mutation, 2-HG levels might play an adverse role in survival, and a more complicated metabolic network might be involved in glioma growth.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Consistent with clinical experience, Tiwari et al [3] found that lower survival risk was associated with higher levels of 2-HG and the presence of IDH mutations. Interestingly, Autry et al [18] revealed that higher levels of 2-HG/Cr indicated a significant reduction in PFS, which contradicts our clinical impression. However, this study enrolled patients with IDH mutations, suggesting that in patients with IDH mutation, 2-HG levels might play an adverse role in survival, and a more complicated metabolic network might be involved in glioma growth.…”
Section: Discussioncontrasting
confidence: 89%
“…After excluding studies evaluating the prognostic value of Cho in gliomas, there was not enough data to conduct a meta-analysis of other metabolites, including Cr [11], lipidlactate [14], lactate [8,9,13], myo-inositol [15], glycine [3], 2-HG [3,18], and glutamate [18]. The associations between these metabolites and prognoses are summarized in Table 3.…”
Section: The Prognostic Value Of Other Metabolites Measured Using 1 H...mentioning
confidence: 99%
See 1 more Smart Citation
“… 30 3D spectroscopy techniques, such as 3D PRESS, echo-planar acquisition with spin-echo excitation (3D-EPSI), and functional spectroscopic mapping (fSM) allow for whole tumor and/or whole brain coverage to fully interrogate irregular and potentially heterogeneous tumors, which should then improve imaging monitoring during treatment. 31–33 Imminent improvements may include matched accumulation and sparse sampling to both reduce scan times (currently 5–15 min) and harness the potential of 7T and higher field strengths.…”
Section: Imaging For Idh Statusmentioning
confidence: 99%
“…30 También puede resultar una infraestimación del mismo en caso de volumen parcial en lesiones de pequeño tamaño y en concentraciones bajas del mismo. 28 Sin embargo surgen posibles soluciones como la utilización de la relación 2HG/Lip+Lact en vez de únicamente el valor absoluto de 2HG para mejorar la sensibilidad y la especificidad, tomando el valor de corte de 0,63 31 y la relación 2HG/Cr con valor de corte de 0,085. 32 El rol de otros metabolitos como predictores de pronostico aún requiere de mucho estudio.…”
Section: Espectroscopía Por Resonancia Magnéticaunclassified